Resilience, mental health and urban migrants: a narrative review. Issue 2 (3rd June 2020) - Coope, Jonathan; Barrett, Andy; Brown, Brian; Crossley, Mark; Raghavan, Raghu; Sivakami, Muthusamy
Abstract : Purpose: The purpose of this paper is to provide a narrative review of the literature on mental health resilience and other positive mental health capacities of urban and internal migrants. Design/methodology/approach: The methodology for this narrative review included a search of articles published up to 2017. The abstracts were screened and relevant articles studied and discussed. Literature on the particular mental health challenges of urban migrants in India was also studied. References found in the literature relating to neurourbanism were also followed up to explore broader historical and conceptual contexts. Findings: Several key sources and resources for mental health resilience were identified – including familial and community networks and individual hope or optimism. Nevertheless, much of the literature tends to focus at the level of the individual person, even though ecological systems theory would suggest that mental health resilience is better understood as multi-layered, i.e. relevant to, and impacted by, communities and broader societal and environmental contexts. Originality/value: This paper provides insight into an aspect of migrant mental health that has tended to be overlooked hitherto: the mental health resilience and positive mental health capacities of urban migrants. This is particularly relevant where professional "expert" mental health provision for internal migrant communities is absent or unaffordable. Previous work has tended to focus predominantly on mental health risk factors, despite growing awareness that focusing on risk factors along can lead to an over-reliance on top-down expert-led interventions and overlook positive capacities for mental health that are sometimes possessed by individuals and their communities.